Mapping the literate lives of two Cameroonian families living in Johannesburg: Implications for language and literacy education - Ngoh, Doris; Kajee, Leila (Per Linguam : A Journal of Language Learning, 2018)
The language and literacy practices of two French-speaking Cameroonian families living in South Africa are the focus of this paper. Since its democracy, there has been an influx of immigrants from all over the world into South Africa. This influx has inevitable consequences for education. The aim of this research was to map the language and literacy practices of two immigrant Cameroonian families residing in Johannesburg, South Africa. The case study utilised interviews with the parents and children, as well as home observations. The research findings reveal that little linguistic congruence exists between the home and school, and that the parents and children serve as language brokers at different points. The study concludes that, if South Africa wants to live up to its democratic status, inclusive to all who live in it, teachers need to be versed in the multiple layers of literacy practices of learners from diverse backgrounds and consider initiatives such as family and community literacy programmes. This is vital not only for immigrant children, but for the South African education system as well.